Fabrication of water-repellent surfaces on galvanized steel. Issue 76 (29th July 2016) - Montes Ruiz-Cabello, F. Javier; Amirfazli, A.; Cabrerizo-Vílchez, M.; Rodríguez-Valverde, M. A.
Abstract : The fabricated superhydrophobic galvanized steel surfaces possess a hierarchic micro/nano texture. Micro-texture is incorporated by sandblasting, while the nano-texture by "soft" acid etching. Abstract : The design of durable superhydrophobic coatings for metal surfaces is a subject of interest and research. Galvanized steel is one of the most used metallic materials for components of automobiles, building structures and roofing. In spite of its wide number of applications, galvanized steel has been scarcely modified to reach superhydrophobicity. The main reason for this is that galvanized steel is essentially a zinc-coated steel surface and most of the strategies to prepare superhydrophobic coatings on metal substrates require partial removal of the surface material. For this reason, providing a non-aggressive strategy to create superhydrophobic galvanized steel (or other metal coated materials) is an important challenge. With this aim, we propose in this paper a methodology based on a two-step texturing process (sandblasting and "soft" acid-etching) followed by a fluoropolymer deposition as a non-invasive strategy to produce water repellent surfaces on this material. The roughness of the samples was analyzed by confocal microscopy and FE-SEM imaging, the surface chemical composition by EDX and the wettability properties by contact angle measurements. Our results show that both texturing methods are necessary to create hierarchically micro/nano-structured surfaces on galvanized steel. This structure induces superhydrophobic properties once the metal is subsequently Teflon-coated. Sandblasting introduces a micro-scale texture, while soft acid-etching incorporates nano-asperities.